Study of Hospital Readiness in Implementing the Standard Inpatient Class (KRIS) Policy at RSUD Bendan Pekalongan City - Mega Prima Nur Fajri; Yuniarti Yuniarti; Teguh Irawan (Jurnal Kesmas Prima Indonesia, 2026)
The Standard Inpatient Class (KRIS) is a policy within the National Health Insurance (JKN) transformation program aimed at achieving equal and standardized inpatient services. Implementation of this policy requires hospital readiness in terms of management and the fulfillment of 12 facility criteria. This study aims to analyze the readiness of KRIS implementation at Bendan Regional Hospital, Pekalongan City, based on management functions. The study used a qualitative descriptive approach through observation, in-depth interviews, and document review with management and related units. The results show that planning has been carried out in stages and based on priorities, organization is carried out through cross-unit coordination, and the implementation of most criteria has been met, especially in bed density, room allocation, room temperature, lighting, and basic facilities. However, several criteria such as ventilation, bed spacing, curtains/partitions, bathrooms, accessibility, and nurse call still require improvement. Control is carried out through internal monitoring and external evaluation, although record keeping still needs to be improved. In general, Bendan Regional Hospital is in the partially ready category for KRIS implementation, so strengthening the roadmap and gradually improving infrastructure is necessary.